2011
DOI: 10.1080/1059924x.2011.605726
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Health and Safety Performance in Australia

Abstract: This study aimed to determine the proportion of Australian farming enterprises with systems and processes that meet current regulatory and industry standards for health and safety. Data from 683 farming enterprises were drawn from a nationally stratified random sample representing seven commodity sectors: beef cattle, cotton, dairy, horticulture, grain growing, sheep, and sugar cane. Results indicated low levels of implementation for farm health and safety plans as well as induction for new workers and contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…While regulation has proven successful in other dangerous industries (e.g., mining and construction) [ 80 ], enforcement in agriculture has proven challenging. Within the farming industry, differences in regulations exist between commodities [ 81 ]. For example, the horticulture, cotton and dairy sectors have higher health and safety performance when compared to other agricultural sectors (e.g., sheep and beef) as they must follow more stringent quality assurance measures [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While regulation has proven successful in other dangerous industries (e.g., mining and construction) [ 80 ], enforcement in agriculture has proven challenging. Within the farming industry, differences in regulations exist between commodities [ 81 ]. For example, the horticulture, cotton and dairy sectors have higher health and safety performance when compared to other agricultural sectors (e.g., sheep and beef) as they must follow more stringent quality assurance measures [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Within the farming industry, differences in regulations exist between commodities [ 81 ]. For example, the horticulture, cotton and dairy sectors have higher health and safety performance when compared to other agricultural sectors (e.g., sheep and beef) as they must follow more stringent quality assurance measures [ 81 ]. Regardless of the presence of similar dangers, small/medium sized farms are less likely to engage in safety measures to protect children than larger farms [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the virtual elimination of farm safety education in Alberta during the late 1990s was not associated with any change in these injury rates. necessarily result in compliance: enforcement is required (Lower, Fragar and Temperley 2011;Finnegan 2007). This accords with the broader literature on OHS legislation (Tompa, Treithick and McLeod 2007).…”
Section: Testing the Narratives "Education Is Preferable To Regulation"mentioning
confidence: 99%
“…No previous studies were found that have specifically evaluated OHSMS interventions in agriculture. However, dairies were found to be one of the top adopters of mandatory OHSMS components as compared to other industries in the Australian agricultural sector (Lower et al, 2011). The International Labour Organization has also included OHSMS guidelines in their most recent Code of Practice on Safety and Health in Agriculture (International Labour Organization, 2010).…”
Section: Introductionmentioning
confidence: 98%